Peran Bank Pembiayaan Rakyat Syariah (BPRS) Dalam Pemberdayaan Ekonomi Masyarakat Bangka Belitung - Ahmad Fauzi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
Community economic decline as a result of commodity prices dropped and the depletion of land for mining and burdensome regulation miners negative impact on revenue Pacific Islands community where the majority of farmers and miners. This is the reason for researchers to examineRole of People's Bank Syariah Financing (SRB) Economic Empowerment In Bangka Belitung. Results from these studies areBank Financing Sharia (SRB) Bangka Belitung in developing the Micro, Small and Medium Enterprises (SMEs) only to providers of financing for communities that need capital to start a business or expand it. Constraints Financing Bank Rakyat Syariah (SRB) Bangka Belitung in developing the Micro, Small and Medium Enterprises (SMEs) which are internal factors such as the collateral for the financing, external factors such as Human Resources (HR) is not much and the government policies that have not been aligned to the bank sharia.